An Investigation of Mineralogy and Microscopic Structure in Kerman City Sediments - Bazanjani, Mohammad Reza Aminizadeh; Lashkaripour, Golam Reza; Ghafoori, Mohammad; Moghadas, Naser Hafezi (International Journal of Geography and Geology, 2013)
In this research, the microscopic structure and mineralogical changes of the soils within Kerman city have been studied. To assess compactness, consolidation and structural characteristics of sedimentary deposits, the authors used the comparing results of scanning electron microscopy (SEM) images in natural and reconstituted soils of Kerman city arena. To study the microstructure of Kerman soils, about 15 soil samples from different depths and locations were prepared and sent to the central electron microscopic laboratory in Ferdowsi University of Mashad. Selected areas were planned in such a way that they have good distribution in Kerman city confine. To understand soil structure some of the samples were reconstituted with moisture content higher than liquid limit as a result of which the post sedimentation structure was demolished. Then images of natural and reconstituted samples were compared with each other. The required tests were performed on samples in Central laboratory of Mashhad University, Iran. Using the energy dispersive X-ray spectroscopy technique (EDX or EDS) chemical composition of the samples was determined to form of point. Having identified the chemical composition of minerals and compared them with typical samples, the name of soil minerals in Kerman soils was determined.